Resistência na Prática de Arquitectura - Ana Varanda Sá Leite Guimarães (2021)
The configuration of capitalism, pressure and acceleration, in an intricate network context and its consequences towards democracy and meritocracy. Understanding the architectural practice as part of a complex organization frame and evolution in which the cult of efficiency grew deeper, mostly as a markets society reflection, and how this affects the relationship between work and worker, product and consumer. Determining key issues before which an architectural practice should question and restructure itself, such as: Scale and Organization; Technique, Technology and Disruption; Form and Formalism; Cost, Value, Quality and Efficiency; Ideology and Cooperation. These were based on the study of the sociology of organizations and the reactionary socialist critique, in which the Arts and Crafts movement was built on. Defining resistance and constant update of organizations through critical theory as well as pragmatic intervention as a possible response to the overwhelming capitalist ramifications. Interseccionality as a main guiding principle towards a social ideology in the 21st century, adding to the search for Equity, Mobility, Permeability, Access and Appropriation. Promoting the dissolution of personal, social and work spheres into one complete and complex agent of resistance.